Drug Discovery for Chagas Disease: Impact of Different Host Cell Lines on Assay Performance and Hit Compound Selection - Caio Haddad Franco; Laura Maria Alcântara; Eric Chatelain; Lucio Freitas-Junior; Carolina Borsoi Moraes (Tropical Medicine and Infectious Disease, 2019)
Cell-based screening has become the major compound interrogation strategy in Chagas disease drug discovery. Several different cell lines have been deployed as host cells in screening assays. However, host cell characteristics and host-parasite interactions may play an important role when assessing anti-T. cruzi compound activity, ultimately impacting on hit discovery. To verify this hypothesis, four distinct mammalian cell lines (U2OS, THP-1, Vero and L6) were used as T. cruzi host cells in High Content Screening assays. Rates of infection varied greatly between different host cells. Susceptibility to benznidazole also varied, depending on the host cell and parasite strain. A library of 1,280 compounds was screened against the four different cell lines infected with T. cruzi, resulting in the selection of a total of 82 distinct compounds as hits. From these, only two hits were common to all four cell lines assays (2.4%) and 51 were exclusively selected from a single assay (62.2%). Infected U2OS cells were the most sensitive assay, as 55 compounds in total were identified as hits; infected THP-1 yielded the lowest hit rates, with only 16 hit compounds. Of the selected hits, compound FPL64176 presented selective anti-T. cruzi activity and could serve as a starting point for the discovery of new anti-chagasic drugs.